The Jukun of Kona, the Emir of Muri and the French adventurer: An oral tradition - Adelberger, Jörg; Storch, Anne (AAeO - Afrikanistik-Aegyptologie-Online, 2008)
Louis Mizon, a Lieutenant of the French Navy, assisted the Emir of Muri, Muhammadu Nya, in conquering the Jukun of Kona in 1892 in an attempt to expand the influence of France in the region of the Benue river. The Emir had besieged Kona in vain for six years, but with the superior military technology at Mizon’s disposal, the town was subjugated. It was a traumatic event which is preserved in the oral traditions of the Jukun until today. The essay presents an oral text recorded in 1996, placing it in the historical context and offering interpretations.